Boards of Directors and Firm Performance: Integrating Agency and Resource Dependence Perspectives - Hillman, Amy J.; Dalziel, Thomas (Academy of Management Review, 2003)
Boards of directors serve two important functions for organizations: monitoring management on behalf of shareholders and providing resources. Agency theorists assert that effective monitoring is a function of a board's incentives, whereas resource dependence theorists contend that the provision of resources is a function of board capital. We combine the two perspectives and argue that board capital affects both board monitoring and the provision of resources and that board incentives moderate these relationships.